Video Transmission Using Device-to-Device Communications: A Survey - Ibtihal Ahmed; Mahmoud H. Ismail; Mohamed S. Hassan (IEEE Access)
In recent years, the growing interest in video-based applications has resulted in a rapid increase in wireless data traffic and meeting the stringent quality-of-experience (QoE) requirements for such type of traffic poses a great challenge given the scarce spectrum. As a consequence, new approaches have been investigated to tackle this problem and one promising solution proposed by researchers is to exploit device-to-device (D2D) communication in video transmission. D2D communication has been presented as an innovation that can improve the cellular network performance by exploiting the proximity-based service between closely-located devices. It enhances the spectral and energy efficiencies, improves the capacity of the network and reduces the communication delay as well. Despite the above-mentioned advantages, there are some challenges in video transmission over D2D networks that need to be addressed. These issues include proposing methods for improving the quality of video streaming, management of the possible resulting interference between the D2D links and regular cellular links, resource allocation as well as appropriate selection of the mode of operation. Besides, issues related to D2D-based video caching such as clustering, energy consumption and the use of incentive-based schemes have also been discussed. In this paper, we examine the challenges of video streaming over D2D networks and comprehensively review the available solutions proposed in the literature.